Analyzing Foucault’s Theory in Digital Security Policy in the Age of AI - Firnando, Hero Gefthi (Austronesia Akademika, 2025)
In the age of artificial intelligence (AI), digital security policies have evolved rapidly, intensifying concerns over surveillance, data control, and state authority. This study examines the relevance of Michel Foucault’s theoretical framework—particularly his concepts of power, biopolitics, and governmentality—in analyzing the structures and implications of contemporary digital security regimes. The widespread adoption of AI technologies in national security initiatives—such as facial recognition, predictive policing, and mass data surveillance—demonstrates a shift in mechanisms of control aligned with Foucault’s notions of disciplinary societies and panopticism. The research aims to critically assess how digital security policies operationalize power through AI, reshaping the dynamics between the state and its citizens. Using a qualitative methodology, the study applies critical discourse analysis to official policy documents, national regulations, and strategic frameworks from selected countries, supported by scholarly and media sources. Findings reveal that such policies often normalize intrusive surveillance practices under the guise of public safety and technological progress, reinforcing asymmetric power relations and challenging democratic accountability. The analysis highlights how algorithmic governance embeds power within technological systems, enabling new forms of control and oversight. Ultimately, the study concludes that applying a Foucauldian lens provides vital insights into the socio-political logics of AI-driven security. It underscores the urgency for transparent, accountable, and rights-based approaches to digital governance in an increasingly automated world.